The limits of the ring image Cherenkov technique - Glässel, Peter (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 1999)
The particle identification performance limits of the ring image Cherenkov technique are discussed both from a principal point of view and with regard to present state-of-the-art technology.
Gesehen am 12.03.2019